Strategi Kepemimpinan Kepala Madrasah Berbasis Entrepreneur di MIN Bancong Wonoasri Madiun - Afifin, yuning Dewi (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2017)
A headmaster is top leader of school had full of responsibility in successes organization he leaded or failure of it. But a headmaster not only has role as a leader but also has role as an entrepreneur in the school. In conducting his role as entrepreneur a headmaster must has a creative and innovative soul. So he makes an education innovation in the school. Headmaster of MIN Bancong Wonoasri Madiun can improve this school both of academic or physic. So the writer interests to writing the paper and conducting MIN Bancong Wonoasri Madiun as a location of research. The method of this research is qualitative method. This research was done at MIN Bancong, Kenanga Street No. 02, RT 02 / RW 02 Bancong Wonoasri Madiun. Techniques of collecting data are: interview, observation and documentation. The data collected was analyzed using the plot: data collection, data reduction, data display, conclusion drawing/verifying. To make sure that the result of this research is the valid result, there was done the credibility test. Finally, the results of this research are: (1) The leadership strategies of entrepreneur had headmaster of MIN Bancong Wonoasri Madiun are: applying fulfill of time behavior, applying fulfill of promise behavior, marketing strategies through the internet, school social responsibility, and conducting the innovation (2) The innovations conducted by headmaster of MIN Bancong Wonoasri Madiun are: curriculum innovation, facility innovation, SDM innovation and administration innovation, (3) the resistances faced headmaster of MIN Bancong Wonoasri Madiun in applying his leaderships’ strategies are: the different of understanding about the important innovation, the different of teachers emotional condition had effect to their working spirit, and the discontinue of fund availability. Keywords: strategi, kepemimpinan, kepala madrasah, entrepreneur.